Rare bird documentation form for Peregrine Falcon at Cou Falls, 1981 - Staudt, Thomas J.et al (1981)
Rare bird documentation form for a Peregrine Falcon at Cou Falls in Johnson County, IA on April 29, 1981. Epson - sheet feed